Synergetic Approach to Agro-industrial Technologies of the Future - Panfilov Viktor A. (Техника и технология пищевых производств)
Introduction. The present research featured some aspects of developing advanced technologies for the future agro-industrial sector of Russia. The paper focuses on a synergistic approach to new complex self-organizing technological systems in food industry. The research objective was to set up scientific foundations for the agro-industrial complex, industrial production of agricultural raw materials of plant and animal origin, and their industrial processing into food. Results and its discussion. The research touched upon the following issues: the conditions for an innovative technological breakthrough into the future of the agro-industrial complex; a dialectic model of technological development; a new industrialization of the agro-industrial complex; the possible economic effect of end-to-end agrifood technologies; the shift from the 4th to the 5th, and eventually to the 6th, techno-economic paradigm in the Russian agro-industrial complex. The article gives a detailed description of the dialectical method, which complicates each technology while simplifying the functioning processes as a whole. Conclusion. Hi-tech development in all branches of Russian agro-industrial complex will make it possible to enter the 6th technoeconomic paradigm and secure domestic food industry in terms of quantity and quality. The article describes prospects of the advanced development of agro-industrial technologies. In addition, it introduces a roadmap for agroscience development: new research should be based on scientific forecasts for the latter half of the XXI century.